PENGARUH BEBERAPA FITOHORMON PADA PEMBENTUKAN MUTAN BARLEY (Hordeum Vulgare) DENGAN FENOTIP BIJI ABNORMAL - Ira N. Djajanegara (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Seg8 is the shrunken endosperm mutant occured naturally in barley (Hordeum vulgare). This recessive mutant does not express xenia which indicates that the endosperm phenotypes depend on the genotype of the diploid maternal parents. This mutant provides an opportunity to analyze factors produced by the female parent that affect the seed development process. One of the factors affecting seed development and growth is phytohormones. In vitro spike culture system adopted from wheat spike culture system was used to investigate the involvement of phytohormones in the grain filling process. Phytohormones were applied during 15 days period of culture. Phytohormones concentrations used were as follows abscisic acid 10–4 M, 5x10–5 M, 10–6M, 5x10–7M and 10–7M. Gibberelic acid concentrations were 5x10–3 M, 5x10–4 M, 5x10–5 M, 2.5x10–5M, 10-5M and 2x10–6M. Cytokinin concentrations were 2x10–6 M, 2x10–7 M and 2x10–8 M. In this experiment, 2 days before anthesis is the best stage to start the spike culture period and 15 days period of culture is sufficient to observe the grain filling process and emergence of the mutant phenotype. The phytohormones treatments as well as their respective concentrations were not able to recover the normal phenotype. Abscisic acid treatment at 5x10-7 M were able to increase the mutant grain dry weight significantly compared to untreated culture but the normal phenotype was not recovered. This indicates that lack of phytohormones was not the maternal factor affecting the seed development process in this particular mutant.